Microsoft Azure Planning, Deploying, and Managing Your Data Center in the Cloud - Copeland, Marshall; Soh, Julian; Puca, Anthony; Manning, Mike.; Gollob, David; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2015)
Written for IT and business professionals, this book provides the technical and business insight needed to plan, deploy and manage the services provided by the Microsoft Azure cloud. Find out how to integrate the infrastructure-as-a-service (IaaS) and platform-as-a-service (PaaS) models with your existing business infrastructure while maximizing availability, ensuring continuity and safety of your data, and keeping costs to a minimum. The book starts with an introduction to Microsoft Azure and how it differs from Office 365—Microsoft’s ‘other’ cloud. You'll also get a useful overview of the services available. Part II then takes you through setting up your Azure account, and gets you up-and-running on some of the core Azure services, including creating web sites and virtual machines, and choosing between fully cloud-based and hybrid storage solutions, depending on your needs. Part III now takes an in-depth look at how to integrate Azure with your existing infrastructure. The authors, Anthony Puca, Mike Manning, Brent Rush, Marshall Copeland and Julian Soh, bring their depth of experience in cloud technology and customer support to guide you through the whole process, through each layer of your infrastructure from networking to operations. High availability and disaster recovery are the topics on everyone’s minds when considering a move to the cloud, and this book provides key insights and step-by-step guidance to help you set up and manage your resources correctly to optimize for these scenarios. You’ll also get expert advice on migrating your existing VMs to Azure using InMage, mail-in and the best 3rd party tools available, helping you ensure continuity of service with minimum disruption to the business. In the book’s final chapters, you’ll find cutting edge examples of cloud technology in action, from machine learning to business intelligence, for a taste of some exciting ways your business could benefit from your new Microsoft Azure deployment.
Part I: Introducing Microsoft Azure -- Chapter 1: Why Choose Microsoft Azure -- Chapter 2: Azure Services Overview -- Chapter 3: Azure Real-World Scenarios -- Chapter 4: Planning Your Azure Deployment -- Part II: Microsoft Azure Quick Start -- Chapter 5: Getting Started with Azure Websites -- Chapter 6: Getting Started with Azure Virtual Machines -- Chapter 7: Understanding Your Storage Options -- Part III: Extending Your On-Premise Environment with Azure -- Chapter 8: Extending Your Network with Azure -- Chapter 9: Identity Management with Azure Active Directory -- Chapter 10: Extending Azure Active Directory -- Chapter 11: Clusters, Regional VNets, High Availability, and Disaster Recovery -- Chapter 12: Migrating Your Virtual Machines to Azure -- Chapter 13: Monitoring and Reporting -- Part IV: Futures and Advanced Topics -- Chapter 14: Machine Learning with Microsoft Azure -- Chapter 15: Data Management and BI with HDInsight -- Chapter 16: Configuring Intune and RMS.
Keywords: Microsoft software; Microsoft .NET Framework; Data structures (Computer science).; Microsoft and .NET.; Data Storage Representation